Professional issues in nursing : challenges and opportunities - Huston, Carol J. (Baltimore, MD ; Philadelphia, PA : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2014)
"Using an approach that fosters critical thinking and values clarification, this textbook examines the full range of professional issues facing contemporary nursing. Coverage includes critical issues such as the nursing shortage, mandatory staffing ratios, violence in nursing, legal and ethical issues, plus the latest HIPAA regulations, career advancement and evaluations, and best practices for today and the future. This edition includes two NEW chapters: 1) a NEW chapter on developing effective leaders to meet 21st century healthcare challenges, and 2) a NEW chapter on the use of residencies for new graduate nurses as a transition to practice. In addition to these exciting additions, content has been updated throughout the book to reflect cutting-edge trends in healthcare including the impact of healthcare reform, and recommendations from the Institute of Medicine (IOM). This edition promises to be an integral tool to providing effective nursing care in an increasingly global, rapidly changing, technology driven world"--Provided by publisher.
I. Furthering the profession. Entry into practice: the debate rages on / Carol J. Huston -- Evidence-based practice / Suzanne S. Prevost -- Developing effective leaders to meet 21st century health care challenges / Bernadette M. Melnyk, Kathy Malloch, Lynn Gallagher-Ford -- Using simulation to teach nurses / Sherry D. Fox, Rebekah Damazo -- II. Workforce issues. The current nursing shortage: causes, consequences, and solutions / Carol J. Huston -- Importing foreign nurses / Carol J. Huston -- Unlicensed assistive personnel and the registered nurse / Carol . Huston -- Socialization and mentoring / Jeanne Madison -- Diversity in the nursing workforce / Carol J. Huston -- New graduate RN transition to practice programs (nurse residencies)/ Deloras Jones, Nikki West -- III. Workplace issues. Mandatory minimum staffing ratios: are they working? / Carol J. Huston -- Mandatory overtime in nursing: how much? how often? / Carol J. Huston -- Violence in nursing: the expectations and the reality / Charmaine Hockley -- Technology in the health care workplace: benefits, limitations, and challenges / Carol J. Huston -- Medical errors: an ongoing threat to quality health care / Carol J. Huston -- IV. Legal and ethical issues. Whistle-blowing in nursing / Carol J. Huston -- Impaired nursing practice: what are we doing about it? / Jennifer Lillibridge -- Collective bargaining and the professional nurse / Carol J. Huston -- Ensuring provider competence through licensure, continuing education, and certification / Carol J. Huston -- V. Professional power. The nursing profession's historic struggle to increase its power base / Carol J. Huston -- Professional identity and image / Carol J. Huston -- Advanced practice nursing: the latest issues and trends / Margaret Rowberg -- Nursing, policy, and politics: understanding the connection and importance of getting involved / Donna M. Nickitas -- Nursing's professional associations / Marjorie Beyers.
Includes bibliographical references and index.
Keywords: NURSING -- UNITED STATES